Enhanced activity and recyclability of palladium complexes in the catalytic synthesis of sodium acrylate from carbon dioxide and ethylene - Manzini, Simone; Cadu, Alban; Schmidt, Anna-Corina; Trapp, Oliver; Schaub, Thomas (ChemCatChem, 2017)
The Pd-catalysed synthesis of sodium acrylate from ethylene and CO2 in the presence of alcoholate bases has been improved significantly. We used amide solvents such as N-cyclohexylpyrrolidone or N,N-dibutylformamide to achieve turnover numbers greater than 500 in one run, which is significantly higher than that of systems for this reaction reported previously. For the first time, we were able to recycle the catalyst without any additional regeneration step. With this system, it is possible to use the simple and easily recycled alcoholate base sodium isopropoxide to achieve good turnover numbers up to 200.